A family empowerment strategy is associated with increased healthcare worker hand hygiene in a resource-limited setting. (February 2020) - Campbell, Jeffrey I.; Pham, Thanh Thuy; Le, Trang; Dang, Thi Thu Huong; Chandonnet, Celeste J.; Truong, Thi Hoa; Duong, Hao; Nguyen, Duc Duat; Le, Thi Huyen; Tran, Thi Ha; Nguyen, Thi Kim Oanh; Ho, Thi Minh Than; et al.
Abstract: Background: Guidelines recommend empowering patients and families to remind healthcare workers (HCWs) to perform hand hygiene (HH). The effectiveness of empowerment tools for patients and their families in Southeast Asia is unknown. Methods: We performed a prospective study in a pediatric intensive care unit (PICU) of a Vietnamese pediatric referral hospital. With family and HCW input, we developed a visual tool for families to prompt HCW HH. We used direct observation to collect baseline HH data. We then enrolled families to receive the visual tool and education on its use while continuing prospective collection of HH data. Multivariable logistic regression was used to identify independent predictors of HH in baseline and implementation periods. Results: In total, 2, 014 baseline and 2, 498 implementation-period HH opportunities were observed. During the implementation period, 73 families were enrolled. Overall, HCW HH was 46% preimplementation, which increased to 73% in the implementation period ( P < .001). The lowest HH adherence in both periods occurred after HCW contact with patient surroundings: 16% at baseline increased to 24% after implementation. In multivariable analyses, the odds of HCW HH during the implementation period were significantly higher than baseline (adjusted odds ratio [aOR], 2.94; 95% confidence interval [CI], 2.54–3.41; P < .001) after adjusting for observation room, HCW type, time of observation (weekday business hours vs evening or weekend), and HH moment. Conclusions: The introduction of a visual empowerment tool was associated with significant improvement in HH adherence among HCWs in a Vietnamese PICU. Future research should explore acceptability and barriers to use of similar tools in low- and middle-income settings.